Ethical challenges and regulatory perspectives of organoids from the results of a Deliberative Workshop (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The article explores some of the issues that arise regarding the use of organoids in clinical and research settings. After introducing the theme of using democratic participation tools in biotechnological contexts, the text addresses some of the main bioethical and biojuridical issues related to organoids through the discussion of the results of a Deliberative Workshop conducted within the Hybrida project – Embedding a comprehensive ethical dimension in organoid-based research and resulting technologies.
Keywords: Organoids; cerebral organoids; partecipatory democracy; deliberative workshop; bioethics